2021
DOI: 10.1352/1934-9556-59.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Are Researchers Addressing Cancer Treatment and Survivorship Among People With Intellectual and Developmental Disabilities in the U.S.? A Scoping Review

Abstract: People with intellectual and developmental disabilities (PWIDD) often encounter barriers in the health care system when seeking general and specialized medical care. Literature has shown that PWIDD experience a lack of proper screening for and prevention of cancer compared to the general population. However, less is known regarding the cancer care and survivorship of PWIDD, especially in the United States. In this review, we examine what is currently known about the primary, psychosocial, and palliative care o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These differences are notable considering that organized population‐based cancer screening programs exist in both provinces in our study. To the best of our knowledge, 6,7,44,45 no other studies have compared the risk of metastatic stage at diagnosis between those living with and without IDD. Our findings are consistent with case reports and case series that suggested potential delays in cancer diagnosis for people with IDD relative to those without IDD, 19–21 as well as lower rates of breast and colorectal cancer screening for individuals with IDD compared to those without IDD 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…These differences are notable considering that organized population‐based cancer screening programs exist in both provinces in our study. To the best of our knowledge, 6,7,44,45 no other studies have compared the risk of metastatic stage at diagnosis between those living with and without IDD. Our findings are consistent with case reports and case series that suggested potential delays in cancer diagnosis for people with IDD relative to those without IDD, 19–21 as well as lower rates of breast and colorectal cancer screening for individuals with IDD compared to those without IDD 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a population-based cohort study in the Netherlands concluded that cancer may be underdiagnosed and/or undertreated in people with intellectual disability 12. A scoping review of cancer treatment and survivorship among people with intellectual and developmental disabilities in the USA reported that urgent action was needed to improve collaboration among healthcare providers 13…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the development and public availability of MHMC, the study team has published 3 manuscripts covering the state of research on cancer screening and treatment for individuals with IDD and the lessons learned from our community-engaged processes [ 45 , 61 - 62 ]. A fourth manuscript sharing detailed results of community-based qualitative formative research has been published [ 50 ], and the results of feasibility and acceptability testing will also be submitted for publication.…”
Section: Discussionmentioning
confidence: 99%